PROPOSAL FOR A LEAN COMMODITY MANAGEMENT PROCESS FOR THE SOUTH AFRICAN NAVY - Carter, Bruce; Slabbert, André (Scientia Militaria - South African Journal of Military Studies, 2011)
Commodity Managers (CMs) within the South African Navy (SAN) need new and innovative ways to achieve effective supply support to their customers. A look at international trends and what other organisations are doing, presents supply support options that will help in formulating an effective commodity management process. The survey, although not an exhaustive benchmarking exercise, does conclude that the process must be clearly defined, visible and comprehensible. Recommended options are presented within four category levels due to the level at which the change or decision can be authorised: ? The national strategic level – Automatic Inventory Replenishment (AIR) and Cost Centre Accounting (CCA). ? The military strategic level – Transportable logistic support and standard containerisation. ? The operational level – Anticipated service life, commercial equipment supportability and outsourcing. ? The tactical level – Repair as a source of supply, Life Cycle Costing (LCC) and critical replenishment procedure. The implementation of any of the recommendations proposed should enhance the supply support activities carried out by CMs. A combination of approved recommendations promises to lead to the formulation of an effective commodity management process that will enhance end-user service delivery, utilising fewer funds and with a reduced staff requirement.